Comet 2P/Encke Observed in Ancient and Medieval Korea (Global Journal of Human-Social Science, 2025)
In this paper, making use of the observational data of Comets observed in Ancient and Mediaeval Korea, we anew elucidated the observational history of the comet 2P/Encke become well known up to now. We found that out of comets corresponding to a few hundred observed in ancient and mediaeval Korea, the observations of comets the periods of which was approximately 3.3year amount to 32 cased. This means that the comet 2P/Encke which had been discovered in AD 1786 in western world had been in AD 54, it had been already observed 32times in Korea up to AD 1638.
Keywords: periodic comet; Encke comet; history of Korea astronomy